Assessment of Bond Strength of Different Bonding Systems to Eroded Dentin Using Sonic Activation: In Vitro Study - Mohammad, Mustafa H.; Thyab, Samer A. (European Journal of General Dentistry, 2024)
Objective Bonding to dentin is a great challenge, and erosion makes it difficult. This study evaluated the effect of sonic agitation on bond strength to eroded dentin using total etch (TE) and self-etch (SE) adhesive systems.Material and Methods A 96-sound human maxillary premolar teeth were prepared to obtain a flat dentin surface, randomly divided into two groups of 48 teeth each. One group was erosive demineralized with 0.05-M citric acid solution to produce an erodedlike dentin surface using de- and remineralization cycles, and the other group was considered a control with no erosive treatment. Each group was bonded with two different bonding strategies, TE (Single Bond 2) and SE (AdheSE One F). Each bonding system was applied with and without sonic activation, and the effect of bond agitation on shear bond strength (SBS) was tested after the application of composite to bonded dentin surface under shear load (0.5 mm/min). Two samples from each group were randomly selected for scanning electron microscopy (SEM) evaluation of the hybrid layer quality. An independent sample t-test was used to assess the effect of erosion, activation, and adhesive type on the SBS. Statistical significance was set at p < 0.05.Result Concerning dentin substrate type, eroded dentin has lower SBS mean values than sound dentin, although it was not significant. Regarding the bonding strategy, TE produced higher SBS values than the SE bonding strategy; it was significant only in sound dentin; despite the bonding strategy and the substrate dentin type, sonic activation produced a significant rise in SBS values except when the SE bonding strategy was applied to eroded dentin where the rise was of no significant value (p > 0.05).Conclusion Sonic agitation effectively improves the SBS value of composite bonded to eroded and sound dentin in both TE and SE strategies.
Keywords: sonic activation; eroded dentin; adhesive system